ANALISIS PENGARUH PROMO SPOT TERHADAP RATING PROGRAM SINETRON (STUDI KASUS PADA STASIUN RCTI) - Chandra, Edward; Tarumingkeng, Rudy C. (Manajemen Bisnis Kompetensi, 2008)
Todays competition in electronic cinema or Ã¢â¬ÅSinetronÃ¢â¬Â, has forced every TV station to apply more precision marketing strategy. One common policy is the promo spot to make a TV station gets higher ratings for their programs. Along with this rating, the advertisers will likely spend their advertising budget to the TV station. This study investigates if there is a strong relationship between the promo spot with the acquisition rating for a TV program. The telecast programs which were broadcasted by Rajawali Citra Televisi Indonesia along the periods of January to June 2007 will be used as the base for researchÃ¢â¬â¢s analysis unit. The result of this study showed that there had been a weak influence between the promo spot and its acquisition rating: 11.4% for January, 1.9% for February, 2.5% for March, 0.3% for April, 3.5% for May and 31.7% for June in the year 2007.Keywords: promo spot, acquisition rating